Development of high-throughput screening method for iron transport inhibitors in E. coli - Hanson, Mathew (Kansas State University, 2015)
Iron acquisition is a component of Gram-negative bacteria pathogenesis, therefore as a form of 'nutritional immunity' host organisms sequester iron. To obtain iron bacteria secrete siderophores that scavenge iron. The E. coli outer membrane protein FepA actively transports the siderophore ferric enterobactin into the periplasm. We observe this uptake reaction by fluorescently labeling FepA in live bacteria, monitoring quenching that occurs upon binding of FeEnt, and then fluorescence recovery during transport. Energy poisons azide, arsenate, and 2,4-dinitrophenol were evaluated to determine sensitivity to known transport inhibitors. We developed and optimized methods to screen for iron transport inhibitors using a cell-based high-throughput screening platform. These inhibitors may have broad spectrum bacteriostatic antibiotic properties.
Keywords: Iron; FepA; TonB; High-throughput screening; Biochemistry; Biochemistry (0487)